Measurement of the differential cross-section of $B^{+}$ meson production in pp collisions at $\sqrt{s}$ = 7 TeV at ATLAS - ATLAS collaboration (2917 authors); Aguilar-Saavedra, Juan Antonio; Amor Dos Santos, Susana Patricia; Anjos, Nuno; Cantrill, Robert; Carvalho, João; Castro, Nuno Filipe; Conde Muiño, Patricia; Da Cunha Sargedas De Sousa, Mario Jose; Do Valle Wemans, André; Fiolhais, Miguel; Galhardo, Bruno; et al. (My University, 2013)
The production cross-section of B+ mesons is measured as a function of transverse momentum pT and rapidity y in proton--proton collisions at center-of-mass energy sqrt(s) = 7 TeV, using 2.4 fb-1 of data recorded with the ATLAS detector at the Large Hadron Collider. The differential production cross-sections, determined in the range 9<pT<120 GeV and y<2.25, are compared to next-to-leading-order theoretical predictions.